Peningkatan Kemampuan Menulis Anak Melalui Permainan Putaran Huruf di Taman Kanak-Kanak - Akmal, Teti; Pransiska, Rismareni (JFACE: Journal of Family, Adult, and Early Childhood Education, 2020)
The purpose of this study was to determine the increase in children's writing skills through the media round letter game. This type of research is a classroom action research (CAR) that uses qualitative and quantitative approaches. The subjects of this study were the teacher and children of B1 Al-Abrar kindergarten with a total of 14 people. The results showed an increase that the ability to write children through the media round letter games has increased. The percentage of mastery learning cycle I only 40%, then in cycle II an increase in children's writing skills through the media round letter game is 86%